ESTIMATING THE PHOTOSYSTEM’S EFFICIENCY, ANTIOXIDANTS ACTIVITY AND PLANT WATER RELATIONS OF TOMATO UNDER WATER DEFICIT CONDITIONS - GHAFFAR, R; SHAHEEN, MR; HUSSAIN, R; ANJUM, S; RASHID, S; SAEED, MA; SHABBIR, A; AMJAD, MU (Biological and Clinical Sciences Research Journal, 2023)
Due to physiological repercussions, the tomato crop has decreased productivity caused by drought throughout its entire life cycle. The tomato harvest has exceeded expectations due to a worldwide water resource limitation. The objective of subjecting the tomato cultivars Flanto and Sahel, to a self-imposed drought was to investigate the interrelationships among biochemical, physiological, enzymatic, and water-related factors. Five varying levels of moisture strongly impacted all plant attributes: 100%, 80%, 60%, 40%, and 20% when subjected to drought stress. The lack of water resulted in notable improvements in some metrics. Some examples of these traits include linear electron flow (LEF), photosynthetic efficiency (PSE), inward light dissipation ratio (qP), catalase activity (CAT), ascorbate peroxidase activity (APX), and leaf water potential (LEWP). Consider, for example, the intriguing discoveries concerning photosystem II, non-photochemical quenching, chlorophyll levels, leaf osmotic potential, and leaf turgor potential.